PENERAPAN METODE RUNGE-KUTTA ORDE 4 MODEL PENYEBARAN DEMAM BERDARAH DENGUE DI KOTA MAKASSAR: Application of The Runge Kutta Method of Order 4 to The Model of The Spread of Dengue Hemorrhagic Fever in Makassar City - Nisa, Sayyidan; Irwan, Irwan; Syata, Ilham (Yayasan Al-Amin Qalbu, 2024)
This research was conducted based on the increasing rate of spread of dengue hemorrhagic fever in the city of Makassar. The aim of this research is to obtain a model for the spread of dengue hemorrhagic fever and find out the numerical solution of the mathematical model. The method used in this research is a quantitative method. The data is processed in the form of quantitative data in the form of the number of people infected, dead and recovered from dengue fever in the city of Makassar in 2021. This research is to predict future dengue hemorrhagic fever cases using the Runge-Kutta Order 4 method. The mathematical model for dengue hemorrhagic fever is in the form of a system of differential equations that includes the variables Sh (Susceptible Host), Ih(Infected Host), Rh (Recovered Host), Sv (Susceptible Vector), dan Iv (Infected Vector). Then look for the parameters that will be used. The research results obtained in january 2022 with Dt = 0,01 using the Fourth Order Runge-Kutta Method with initial values of Sh0= 1426454, Ih0 = 583, Rh0 = 582, Sv0 = 13165, Iv0 = 1215 is Sh100 = 1420142, Ih100 = 2949, Rh100 = 4529, Sv100 = 13706, Iv100 = 751.